Relative Clause Attachment Ambiguity Resolution in L1-Persian Learners of L2 English: The Effects of Semantic Priming and Proficiency - Mohammad Nabi Karimi; Eskandar Samadi; Esmat Babaii (Journal of Modern Research in English Language Studies)
The present study explored the effect of semantic priming in the resolution of ambiguous sentences containing Relative Clauses (RCs) preceded by a complex Noun Phrase (NP) by L1-Persian learners of L2 English. The type of semantic relationship examined was the one between the RC and one of the NPs in the complex NP to find out whether semantic manipulation through priming one of the NPs to the RC can affect L2 learners’ attachment preference. The participants were 60 L1-Persian learners of L2 English with different proficiency levels. In a self-paced Paraphrase Decision Task using E-prime software, their reading times and attachment preferences while reading ambiguous sentences were examined. The low-proficiency participants’ off-line (RC attachment preferences) and on-line data (reading times) were compared with off-line and on-line data obtained from high-proficiency participants. The results revealed that in both groups, semantic priming affected participants’ attachment preferences. These findings are consistent with Constraint-based Models of sentence processing, which assume that several sources of information, including semantics, are used in sentence processing. The results also support predictions of the Spreading Activation Model. There were also significant differences between the two groups, low-proficiency participants fully transferred their L1 (Persian) processing strategies to their L2 (English). However, high-proficiency participants processed sentences similarly to native English speakers even though there were still traces of their L1 parsing preferences which is consistent with Shallow Structure Hypothesis.